Electrical Stimulation by an Organic Transistor Architecture Induces Calcium Signaling in Nonexcitable Brain Cells. Issue 3 (19th December 2018) - Borrachero‐Conejo, Ana Isabel; Saracino, Emanuela; Natali, Marco; Prescimone, Federico; Karges, Saskia; Bonetti, Simone; Nicchia, Grazia Paola; Formaggio, Francesco; Caprini, Marco; Zamboni, Roberto; Mercuri, Francesco; Toffanin, Stefano; et al.
Abstract: Organic bioelectronics have a huge potential to generate interfaces and devices for the study of brain functions and for the therapy of brain pathologies. In this context, increasing efforts are needed to develop technologies for monitoring and stimulation of nonexcitable brain cells, called astrocytes. Astroglial calcium signaling plays, indeed, a pivotal role in the physiology and pathophysiology of the brain. Here, the use of transparent organic cell stimulating and sensing transistor (O‐CST) architecture, fabricated with N, N′ ‐ditridecylperylene‐3, 4, 9, 10‐tetracarboxylic diimide (P13), to elicit and monitor intracellular calcium concentration ([Ca 2+ ]i ) in primary rat neocortical astrocytes is demonstrated. The transparency of O‐CST allows performing calcium imaging experiments, showing that extracellular electrical stimulation of astrocytes induces a drastic increase in [Ca 2+ ]i . Pharmacological studies indicate that transient receptor potential (TRP) superfamily are critical mediators of the [Ca 2+ ]i increase. Experimental and computational analyses show that [Ca 2+ ]i response is enabled by the O‐CST device architecture. Noteworthy, the extracellular field application induces a slight but significant increase in the cell volume. Collectively, it is shown that the O‐CST is capable of selectively evoking astrocytes [Ca 2+ ]i, paving the way to the development of organic bioelectronic devices as glial interfaces to excite and control physiology of non‐neuronal brain cells. Abstract : Calcium signalling ([Ca 2+ ]i ) of non‐excitable brain cells called astrocytes plays a pivotal role in brain function and dysfunction. This work demonstrates the use of organic cell stimulating and sensing transistor (O‐CST) to alter [Ca 2+ ]i and the functionality non‐excitable brain cells, by an extracellular electric field. The major involvement of transient receptor potential channels in the molecular mechanism underpinning the response are identified.